Analysis of Strategic HR Business Partners and Managerial Competencies on the Effectiveness of HR Management in the Manufacturing Industry in Karawang - Anung Haryanto; Salwa Aulia Novitasari; Sintia Permata Sari (West Science Interdisciplinary Studies, 2026)
This study examines the role of Strategic Human Resource Business Partner (Strategic HRBP) and managerial competencies in improving HR management effectiveness in manufacturing companies in Karawang, West Java. A quantitative approach with a cross-sectional survey design was employed. Data were collected from 135 respondents working in manufacturing companies using a structured questionnaire measured on a five-point Likert scale. The data were analyzed using IBM SPSS Statistics version 25 through descriptive statistics, validity and reliability testing, classical assumption tests, Pearson correlation, multiple linear regression, t-tests, F-tests, and coefficient of determination. The results show that Strategic HRBP has a positive and significant effect on HR management effectiveness. Managerial competencies also have a positive and significant effect. Simultaneously, both variables significantly influence HR management effectiveness, as indicated by F = 70.501 and p < 0.001. The model explains 51.6% of the variance in HR management effectiveness (R² = 0.516). Managerial competencies show a slightly stronger contribution than Strategic HRBP. These findings indicate that effective HR management in manufacturing organizations requires both strategic integration of the HR function and competent managerial execution. Strengthening HR business partnering and managerial capabilities can therefore support more responsive, strategically aligned, and effective human resource management.